Pengenalan Perangkat Keras Komputer TIK melalui Media Gambar pada Siswa SB Kamus Gombak Utara - Febriyanti, Elsa; Nur, Hana Astria; Hadiana, Oman; Heriyana, Tio; Casnan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Educational technology helps facilitate the learning process and improve student performance by utilizing the right technology. This is important to accelerate learning and assist teachers in time management. Educational technology includes the development of tools that can improve learning abilities and use test results as indicators of student achievement, interesting learning media can motivate students to be more active. On December 5, 2023, at the Sanggar Bimbingan Kamus Gombak Utara, I conducted a socialization about computer hardware for fifteen grade VI students. Before the activity, students had difficulty understanding technology, especially the basics of computer components. To overcome this, I used a media-based learning method, which helped students recognize hardware visually. The results were very satisfying, with an increase in the average student score from 38.75 to 88.75, this means an increase of 50 points (129%). The type of media used was labeled illustration images, which aimed to show the various components of computer hardware along with their names and descriptions. This labeling activity was added to increase interactivity, where students were invited to meet the names of the components with the corresponding images. This approach helps students better recognize and understand computer hardware. This activity also includes presentations and discussions on Information and Communication Technology (ICT). With interactive methods, students are expected to be better prepared to face future challenges and be able to utilize technology for better communication and access to information.